Predicting Adverse Pathologic Features and Clinical Outcomes of Resectable Pancreas Cancer With Preoperative CA 19-9 - Kowalchuk, Roman O.; Lester, Scott C.; Graham, Rondell P.; Harmsen, William S.; Zhang, Lizhi; Halfdanarson, Thorvardur R.; Smoot, Rory L.; Gits, Hunter C.; Ma, Wen Wee; Owen, Dawn; Mahipal, Amit; Miller, Robert C.; et al. (Frontiers in Oncology, 2021)
Background: We evaluated preoperative CA 19-9 levels in patients with resected pancreatic cancer to analyze whether they were predictive of clinical outcomes and could help select patients for additional therapy. We hypothesized that elevated CA 19-9 would be associated with worse pathologic findings and oncologic outcomes. Methods: This study assessed 509 patients with non-metastatic pancreatic adenocarcinoma who underwent resection at our institution from 1995-2011 and had preoperative CA 19-9 recorded. No patients received neoadjuvant therapy. CA 19-9 level was analyzed as a continuous and a dichotomized (> vs. ≤ 55 U/mL) variable using logistic and Cox models. Results: Median follow-up was 7.8 years, and the median age was 66 years (33-90). 64% of patients had elevated preoperative CA 19-9 (median: 141 U/mL), that did not correlate with bilirubin level or tumor size. Most patients had ≥ T3 tumors (72%) and positive lymph nodes (62%). The rate of incomplete (R1 or R2) resection was 19%. Increasing preoperative CA 19-9 was associated with extra-pancreatic extension (p=0.0005), lymphovascular space invasion (p=0.0072), incomplete resection (HR [95% CI] 2.0 [1.2-3.5]), and lower OS (HR=1.6 [1.3-2.0]). Each doubling in preoperative CA 19-9 value was associated with an 8.3% increased risk of death (HR=1.08 [1.02-1.15]) and a 10.0% increased risk of distant recurrence (HR=1.10 [1.02-1.19]). Patients classified as non-secretors had comparable outcomes to patients with normal CA 19-9. Conclusions: Elevated preoperative CA 19-9 level was associated with adverse pathologic features, incomplete resection, and inferior clinical outcomes. Neither tumor size nor bilirubin confound an elevated CA 19-9 level. Preoperative CA 19-9 level may help select patients for additional therapy.